Each baby counts: National quality improvement programme to reduce intrapartum-related deaths and brain injuries in term babies. Issue 3 (June 2017) - Robertson, Louise; Knight, Hannah; Prosser Snelling, Edward; Petch, Emily; Knight, Marian; Cameron, Alan; Alfirevic, Zarko
Abstract: Although the most recent MBRRACE-UK (Mothers and Babies: Reducing Risk through Audits and Confidential Enquiries across the UK) perinatal mortality report has shown a downward trend in perinatal mortality, the UK still lags behind the best-performing countries in Europe. The burden of perinatal morbidity and mortality is wide-reaching and devastating for the families and care-providers involved. The aim of the Each Baby Counts (EBC) project is to reduce intrapartum term stillbirths, early neonatal deaths, and severe brain injuries by 50% by 2020. Every maternity care provider has been asked to report their intrapartum term stillbirths, early neonatal deaths and severe brain injuries to the EBC project and provide a copy of the local review. The local reviews are assessed by two trained EBC reviewers in order to establish whether the reviews are of adequate quality. The EBC reviewers are asked independently to assess whether there is sufficient clinical information to make a clinical judgement about care, and whether different care could have had a positive impact on the outcome. The reviewers are asked to indicate in what areas care might be improved. The analysis of the local reports will be twofold. Initially quantitative analysis will provide us with information about the scale of the problem, the quality of the local review process into adverse events, and who is involved in such reviews. Qualitative analysis of the themes highlighted in the reviews will enable us to develop care bundles or other tools to drive local quality improvement.